Beragama Katolik, Berbudaya Tionghoa sebuah Kajian Terhadap Hibriditas Umat Katolik-Tionghoa Paroki St. Maria Immaculata Slawi - Julianto, Romario; Lelono, Martinus Joko (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2024)
Santa Maria Immaculata Slawi Parish stands in the Tegal Regency area which has a history of the development of the Chinese community. Chinese ethnicity plays an important role in the dynamics of the Parish. They simultaneously live Chinese culture and the Catholic faith. As a result of the New Order policies they were unable to live out their culture, but Presidential Decree Number 6 of 2000 and Presidential Decree Number 19 of 2000 opened up space for their cultural expression. On Chinese New Year they start holding toa pek kong or tepekong mutual carnivals. The gotong tepekong ritual is a procession of palanquins containing statues of ancestors that are paraded around the city. This article will explore the appreciation of Chinese Catholics in living out two different traditions. Homi K. Bhabha's thoughts are used to understand the attitude choices of the Chinese-Catholic community in Slawi. In his study, Homi K. Bhabha talks about "third space," the meeting or interaction between two different cultures or identities in the same space. Homi K. Bhabha emphasizes "third space" not only as a result of the meeting between two cultures but also as a dynamic social construction. Analysis of this reality will help understand the complexity of people's meaning of their religious and cultural riches.AbstrakParoki Santa Maria Immaculata Slawi berdiri di daerah Kabupaten Tegal yang memiliki sejarah berkembangnya masyarakat Tionghoa. Etnis Tionghoa berperan penting dalam dinamika Paroki. Mereka sekaligus menghidupi budaya Tionghoa dan iman Katolik. Akibat kebijakan orde baru mereka tidak bisa menghidupi budaya mereka, tetapi Keputusan Presiden Nomor 6 Tahun 2000 dan Keputusan Presiden Nomor 19 Tahun 2000 membuka ruang bagi ekspresi budaya mereka. Pada Tahun Baru Imlek mereka mulai mengadakan kirab gotong toa pek kong atau tepekong. Ritual gotong tepekong merupakan arak-arakan tandu yang berisikan patung leluhur yang diarak mengelilingi kota. Tulisan ini akan menggali penghayatan orang Katolik-Tionghoa dalam menghidupi kedua tradisi yang berbeda. Pemikiran Homi K. Bhabha digunakan untuk memahami pilihan sikap umat Tionghoa-Katolik di Slawi. Dalam kajiannya, Homi K. Bhabha berbicara mengenai “ruang ketiga,” pertemuan atau interaksi antara dua budaya atau identitas yang berbeda dalam satu ruang yang sama. Homi K. Bhabha menekankan “ruang ketiga” bukan hanya sebagai hasil pertemuan antara dua budaya melainkan juga membangun konstruksi sosial yang dinamis. Analisis terhadap realitas ini akan membantu memahami kompleksitas pemaknaan umat akan kekayaan agama dan budayanya.